Mycobacterium bovis BCG killed by extended freeze‐drying induces an immunoregulatory profile and protects against atherosclerosis. (12th September 2013) - Ovchinnikova, O. A.; Berge, N.; Kang, C.; Urien, C.; Ketelhuth, D. F. J.; Pottier, J.; Drouet, L.; Hansson, G. K.; Marchal, G.; Bäck, M.; Schwartz‐Cornil, I.; Lagranderie, M.
Abstract Objectives Atherosclerosis is an inflammatory disease of the arterial wall that leads to myocardial infarction and stroke. Regulatory T cells (Tregs) and IL‐10 exert significant anti‐atherogenic effects in experimental models of atherosclerosis by modulating vascular inflammation. We have previously shown that Mycobacterium bovis BCG killed by extended freeze‐drying (EFD BCG) decreases lung and colon inflammation by recruiting IL‐10‐producing Tregs. Therefore, the aim of this study was to investigate the effect of EFD BCG on the development of atherosclerosis. Design We used two strains of atherosclerosis‐prone mice: Ldlr−/− (four or six EFD BCG injections) and Apoe−/− (six injections). Results In both models, EFD BCG significantly reduced the size of atherosclerotic lesions, increased IL‐10 production and reduced the serum levels of pro‐inflammatory cytokines (IL‐6, IL‐13, KC and tumour necrosis factor‐α). Shortly after treatment with EFD BCG, the number of plasmacytoid dendritic cells (pDCs) and Foxp3+ Tregs in the draining lymph nodes increased. EFD BCG also led to accumulation of Tregs, but not of pDCs in the spleen, and reduced activity of NF‐κB and increased activity of PPAR‐γ in both the spleen and vascular tissue of treated mice. Conclusion EFD BCG has atheroprotective effects through IL‐10 production and Treg expansion. These findings support a novel approach to the prevention and treatment of atherosclerosis.